A conceptual framework for evaluation of information technology investments. (1st January 2002) - Sylla, Cheickna; Wen, H. Joseph
The decision to acquire a new information technology poses a number of serious evaluation and selection problems to technology managers, because the new system must not only meet current information requirements of the organisation, but also the needs for future expansion. Tangible and intangible benefits factors, as well as risks factors, must be identified and evaluated. The paper provides a review of ten major evaluation categories and available models, which fall under each category, showing their advantages and disadvantages in handling the above difficulties. This paper describes strategic implications involved in the selection decision, and the inherent difficulties in: (1) choosing or developing a model, (2) obtaining realistic inputs for the model, and (3) making tradeoffs among the conflicting factors. It proposes a conceptual framework to help the decision maker in choosing the most appropriate methodology in the evaluation process. It also offers a new model, called GAHP, for the evaluation problem combining integer goal linear programming and Analytic Hierarchy Process (AHP) in a single hybrid multiple objective multi-criteria model. A goal programming methodology, with zero-one integer variables and mixed integer constraints, is used to set goal target values against which information technology alternatives are evaluated and selected. AHP is used to structure the evaluation process providing pairwise comparison mechanisms to quantify subjective, nonmonetary, intangible benefits and risks factors, in deriving data for the model. A case illustration is provided showing how GAHP can be formulated and solved.